2015
DOI: 10.1007/s13277-015-4679-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABCB1 and ABCG2 single nucleotide polymorphisms with clinical findings and response to chemotherapy treatments in Kurdish patients with breast cancer

Abstract: The possible interaction between gene polymorphisms and risk of cancer progression is very interesting. Polymorphisms in multi-drug resistance genes have an important role in response to anti-cancer drugs. The present study was aimed to evaluate the possible effects of ABCB1 C3435T and ABCG2 C421A single nucleotide polymorphisms on clinical and pathological outcomes of Kurdish patients with breast cancer. One hundred breast cancer patients and 200 healthy controls were enrolled in this case-control study. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…On the other hand, the authors suggested strong linkage disequilibrium with other polymorphisms in ABCB1 gene and alterations in the post translational pathway which influences the efficacy and stability of P-gp in patients with CC genotype [26]. Similarly, in Kurdish patients the frequency of CC genotype and C allele were higher in patients than in controls; this result was not statistically significant [25]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the authors suggested strong linkage disequilibrium with other polymorphisms in ABCB1 gene and alterations in the post translational pathway which influences the efficacy and stability of P-gp in patients with CC genotype [26]. Similarly, in Kurdish patients the frequency of CC genotype and C allele were higher in patients than in controls; this result was not statistically significant [25]. …”
Section: Discussionmentioning
confidence: 99%
“…In this line, Turgut et al [13], Wu et al [20] and Macías-Gómezdid et al [23] have reported similar results. However, Ghafouri et al have found a significant correlation between ABCB1 C3435T polymorphism and clinical grades of breast cancer with higher grade in CC carriers ( P  = 0.027) [25]. On the other hand, Wu et al [20] observed that patients with a negative status of ER and PR have more CT + TT genotypes than CC genotype ( P  = 0.013).…”
Section: Discussionmentioning
confidence: 99%
“…In Q141K-expressing cell lines, daunorubicin and doxorubicin were found to show increased accumulation compared with wild type (Tamura et al, 2007b), but worse outcomes were shown in Q141K acute myeloid leukemia patients treated with idarubicin (Tiribelli et al, 2013). In addition, the presence of the 421C allele was indicative of a weaker treatment response to anthracyclines in a Kurdish population (Ghafouri et al, 2016). The same study showed Q141K produced a weaker response to the taxane paclitaxel (Ghafouri et al, 2016), although Q141K patients were associated with longer progression-free survival when treated with paclitaxel and platinum therapy in a study on ovarian cancer patients (Tian et al, 2012).…”
Section: Q141k (Rs2231142)mentioning
confidence: 97%
“…In addition, the presence of the 421C allele was indicative of a weaker treatment response to anthracyclines in a Kurdish population (Ghafouri et al, 2016). The same study showed Q141K produced a weaker response to the taxane paclitaxel (Ghafouri et al, 2016), although Q141K patients were associated with longer progression-free survival when treated with paclitaxel and platinum therapy in a study on ovarian cancer patients (Tian et al, 2012). Another taxane, docetaxel, was shown in a recent study to have reduced resistance in Q141K carriers compared with wild type (Sobek et al, 2017), despite Q141K previously having been shown to have no influence on docetaxel disposition (Baker et al, 2009;Chew et al, 2011).…”
Section: Q141k (Rs2231142)mentioning
confidence: 99%
“…The molecular mechanism of disease development has not yet been fully understood, attention is paid to the simultaneous participation of many environmental and genetic factors. Genetic variants like SNPs may be a protective or risk factor in the cancer development and be correlated with response to chemotherapy [5,6].…”
Section: Introductionmentioning
confidence: 99%